Photocatalytic activity and mechanism of YMnO3/NiO photocatalyst for the degradation of oil and gas field wastewater - Zhu, Jiang; Cheng, Xiaoyi; Cui, Yajing; Chen, Feng (Frontiers in Chemistry, 2024)
One-step hydrothermal method has been used to synthesize YMnO3@NiO (YMO@NO) photocatalysts with high photocatalytic activity for the degradation of oil and gas field wastewater under simulated solar irradiation. Through various characterization methods, it has been confirmed that the YMO@NO photocatalyst comprises only YMO and NO, without any other impurities. The microstructure characterization confirmed that the YMO@NO photocatalyst was composed of large squares and fine particles, and heterojunction was formed at the interface of YMO and NO. The optical properties confirm that the YMO@NO photocatalyst has high UV-vis optical absorption coefficient, suggesting that it has high UV-vis photocatalytic activity. Taking oil and gas field wastewater as degradation object, YMO@NO photocatalyst showed the highest photocatalytic activity (98%) when the catalyst content was 1.5 g/L, the mass percentage of NO was 3%, and the irradiation time was 60 min. Capture and stability experiments confirm that the YMO@NO photocatalyst is recyclable and electrons, holes, hydroxyl radicals and superoxide radicals play major roles in the photocatalysis process. Based on experiments and theoretical calculations, a reasonable photocatalytic mechanism of the YMO@NO photocatalyst is proposed.